Admission platelet count and indices as predictors of outcome in children with severe Sepsis: a prospective hospital-based study - Samira Z. Sayed; Mohamed M. Mahmoud; Hend M. Moness; Suzan O. Mousa (BMC, 2020)
Abstract Background Sepsis is still one of the main causes of infants and children mortality especially in developing, economically challenged countries with limited resources. Our objective in this study was to determine, the prognostic value of platelet count, mean platelet volume (MPV), platelet distribution width (PDW) and plateletcrit (PCT) in critically ill infants and children with severe sepsis, as they are readily available biomarkers, that can guide clinicians during managing of severe sepsis. Methods Sixty children were included; they were diagnosed with severe sepsis according to the international pediatric sepsis consensus conference criteria. At admission to Pediatric intensive care unit, complete blood count with platelet count and parameters (MPV, PDW and PCT) and C-reactive protein (CRP) level were determined for all children. Also, assessment of the Pediatric Risk of Mortality (PRISM III) score was done to all. These children were followed up till discharge from hospital or death. Accordingly, they were grouped into: (1) Survivor group: included 41 children. (2) Non-survivor group: included 19 children. Results Platelet count and PCT were significantly lower (p < 0.001) and MPV was significantly higher in non-survivor than survivors (p = 0.004). MPV/PLT, MPV/PCT, PDW/PLT, PDW/PCT ratios were found to be significantly higher in the non-survivors than survivor (p < 0.001 in all). PCT with sensitivity = 94.74%, was the most sensitive platelet parameter for prediction of death, while MPV/PCT was the most sensitive ratio (sensitivity = 94.7%). Conclusion Thrombocytopenia, platelet indices and their ratios, especially plateletcrit and MPV/PCT, are readily available, sensitive, prognostic markers, that can identify the severe sepsis patients with poorest outcome.